Potential for pharmacist prescribing in primary care: A Dutch citizen perspective - Thomas G.H. Kempen; Liset van Dijk; Annemieke Floor-Schreudering; Aradhana Kohli; Henk-Frans Kwint; Laura Schackmann; Lilian H.D. van Tuyl; Mette Heringa (Elsevier, 2024)
Background: Medication prescribing by pharmacists is a task shifting approach to help ensure quality and accessibility of healthcare. In many countries, like the Netherlands, pharmacist prescribing is not legally ensured, and it is unknown what citizens think of its potential introduction. Objective: To investigate citizen perspectives on the potential role of pharmacists in prescribing in primary care. Methods: A Citizen Platform with citizens (>18 years) from the Netherlands was conducted in October 2022. This consisted of a one-day program in which the participants were engaged in interactive assignments and received expert presentations to foster the development of informed opinions. In the final assignment, 3 participant groups designed their ideal future scenario including preconditions regarding the role of the pharmacist in prescribing in primary care. All assignments were recorded, and notes were taken. The researchers then consolidated the 3 scenarios into one version and categorized the preconditions. The Citizen Platform results were summarized and subsequently discussed in 2 online focus groups with other citizens in February 2023 to investigate the perspectives of less informed citizens. Focus group discussions were audio-recorded, transcribed, and thematically analyzed. Results: The Citizen Platform (n = 10) resulted in a shared scenario involving a primary care center where general practitioners (GPs) pharmacists and other healthcare professionals collaborate as a team. In this scenario, pharmacists can modify treatment in certain chronic diseases, manage minor ailments and support GPs with the care for patients with complex needs. Preconditions needed to realize this scenario include having shared medical records, the GP retaining the overview of the care for the patient and additional training for pharmacists. The focus groups (n = 6, in total) yielded 5 themes which acknowledge potential pharmacist prescribing but depict a more skeptical view towards pharmacist prescribing and include several concerns, for example pharmacists' potential conflict of interest. Conclusions: Citizens that are informed about opportunities for pharmacy prescribing are capable of sketching potential scenarios for pharmacist prescribing in a collaborative primary care context. Less informed citizens seem more skeptical towards pharmacist prescribing.